The Suffering with God Scale: Theoretical Development, Psychometric Analyses, and Relationships with Indices of Religiosity - Webb, Marcia (Research in the social scientific study of religion, 2010)
religion provides resources to cope with negative life events, yet people may still struggle with god. The Suffering with god Scale (Swg) was developed to assess schematic representations of, and affective responses to, god in light of negative life events. exploratory factor analysis resulted in a two-factor solution reflecting two underlying dimensions: Struggling with God and Enduring with God. Struggling was negatively associated, and Enduring was positively associated, with theism, religious participation, personal devotions, and intrinsic religiosity. persons who were unsure of their faith reported greater struggle than those reporting high or low faith. results are interpreted in light of psychology of religion research and theological reflection regarding the problem of suffering for sustenance of faith.